ANALISIS HUKUM ISLAM TERHADAP PRAKTEK JUAL BELI SALAM DAN IJON DALAM MAQASHID SYARI???AH - Muhammad Yusup (Al-Iqtishad: Jurnal Ekonomi Syariah, 2021)
In some areas, the practice of Ijon is common, namely selling fruit on unfruitful trees. Say, two months before the mango season, the vendor has paid for the purchase of mangoes. Now when the harvest season arrives, whatever number of mangoes are on the tree belongs to the pengijon. This kind of buying and selling is prohibited in Islam because it is not clear how many items are being traded. In principle, Islam prohibits buying and selling goods that do not yet exist, even if there are exceptions, it is bai' (buying and selling) greetings with certain limitations. Bai' salam is a sale and purchase with the condition that the buyer pays now for the goods that he will receive in the future. In the example above, the purchase of mangoes before harvest is legal if the quantity, quality, and delivery time are determined. For example, "I bought 100 kg of Arumanis mangoes, I pay now for 2000 per kg and I will receive the mangoes in the next two months". The practice of bai 'salam like this was found in the people of Medina at the time of the Prophet Muhammad. In Islamic Fiqh, bai' salam is also called bai' salaf or bai' mafalis (al-Kasani, Bidai al Kasani fi tartib al muqtasid, V; 201). When the Prophet migrated to Medina, he met many people who traded in the salaf for a period of two and three years. Regarding the practice of buying and selling in the salaf, the Messenger of Allah said, "Whoever performs the salaf, he must do it for goods of clear weight and size and for a definite period of time" (Bukhori, Kitab As Salam: Abu Dawud, Kitab Al Buyu). Most of the bai' salam that was done at that time was to meet the needs of farmers and traders (Ibn Qudamah, al Mughni, IV: 275, Zalai, Nasabal Ra'yah lil Hadith al Hidayah, IV; 42). In addition, this paper also lists several views of Islamic scientists and several fatwas related to the status of the practice of Ijon and Ba'I salam according to sharia and analyzes the relevance of their practice from the perspective of Maqoshid Sharia. The results of this discussion explain the arguments and causes as well as the law of the practice of Ijon and Bai' salam according to Shariah.